Stakeholder perceptions of family friendly workplaces : case studies of six New Zealand organisations : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Business Studies at Massey University - Liddicoat, Linda (Massey University, 1999)
A family friendly workplace is one in which management finds out what would help employees balance work and family responsibilities, and implements appropriate family friendly policies and practices. A variety of family friendly practices or initiatives exist, including flexible working hours, flexible leave, work from home, parental leave and childcare. Family friendly workplace initiatives help both employers and employees. Employer benefits include enhanced staff recruitment and retention, reduced staff turnover, reduced absenteeism, increased employee morale and an enhanced company image. Employees receive help in balancing work and family responsibilities, and enjoy greater control or autonomy in balancing these responsibilities. The literature identifies a number of workplace changes that have prompted the development of family friendly workplaces, including increasing numbers of women and mothers participating in the workforce, and changes in the composition of families, in legislation and in the workplace itself. A number of theories explain the relationship between work and home, the three most commonly cited being segmentation, spillover and compensation. The literature also demarcates stages in the development of family friendly workplaces, and emphasises the importance of a supportive organisation culture to the successful development of a family friendly workplace. Potential barriers to the successful development and implementation of family friendly workplaces include the masculine work ethic, the notion that organisations should not involve themselves in the private lives of their employees, and the issue of 'face time'. Two additional issues the literature addresses are determining who should be responsible for the provision of family friendly initiatives, and identifying critical success factors. There have been a number of overseas studies (e.g., Galinsky, Friedman & Hernandez, 1991; Milliken, Dutton & Beyer, 1990; Rappoport & Bailyn, 1996) which have examined family friendly workplace policies and practices. However in the New Zealand context, the area of work and family has not been sufficiently researched or understood. To date in New Zealand there have only been five major studies on family friendly workplaces (Callister, 1996; Families at Work & Top Drawer Consultants, 1995; Ministry of Women's Affairs, 1993; Top Drawer Consultants & Families at Work, 1996; Tudhope, 1994), and although each study has made a contribution to the knowledge of family friendly workplaces in the New Zealand context, many gaps still remain. This current study is the first New Zealand study in the area of work and family to explore the perceptions of both employers (managers) and employees, as well as to integrate the perceptions of CEOs, union officials and other organisation stakeholders. By aligning the perceptions of these organisation stakeholders, this study was able to examine whether they reported similar or differing perceptions of family friendly workplaces. Finally, the importance of these similarities and differences and their possible impact on family friendly workplace initiatives is discussed. Participants in this research project included employees, human resource managers, CEOs, union officials and selected organisation stakeholders in six New Zealand organisations. Employees responded to a questionnaire; others participated in interviews. The major findings are as follows: flexibility to enable employees to balance their work and family responsibilities was deemed the most important family friendly initiative by both employees and human resource managers; employees reported a lack of consultation prior to the implementation of family friendly initiatives and inadequate ongoing consultation. However, human resource managers tended to believe consultation occurred throughout; many employees were unaware of family friendly initiatives offered within the organisation; employees reported that the primary sources of information on family friendly initiatives available within the organisation were managers and colleagues; most employees agreed that family friendly initiatives were applied consistently within the organisation; a number of male employees indicated they were caregivers of dependants and needed access to family friendly initiatives to help them balance their work and family commitments; informal childcare, including the use of relatives or friends as carers, was an important means of care for many employees; managerial motivation to introduce family friendly initiatives included requests from staff, and the need to address high staff turnover; developing an organisation culture that supports employees with family responsibilities was identified as important to the success of a family friendly workplace; and some discrepancies emerged between the responses of the different participant groups, including differing views of the consultation process, differing perceptions of the dissemination of information on family friendly initiatives within the organisation, and the rating of each organisation's family friendliness. This study is the first New Zealand study to align the perceptions of organisation stakeholders and to explore similarities and differences between each of the stakeholder groups. Thus, the study adds to the overall understanding of family friendly workplaces, while it identifies key issues related to the success of family friendly initiatives in New Zealand.
Keywords: Employee assistance programmes; Corporate culture; Family-friendly workplaces; Case studies; Public opinion; New Zealand